Bibliometric and visual analysis of coronary microvascular dysfunction - Xiaoxiao Lin; Guomin Wu; Beibei Gao; Shuai Wang; Jinyu Huang (Frontiers in Cardiovascular Medicine, 2022)
BackgroundCoronary microvascular dysfunction (CMD) may play an important role in various cardiovascular diseases, including HFpEF and both obstructive and non-obstructive coronary artery disease (CAD). To date, there has been no bibliometric analysis to summarize this field. Here, we aim to conduct a bibliometric analysis of CMD to determine the current status and frontiers in this field.Materials and methodsPublications about CMD were taken from the Web of Science Core Collection database (WOSCC). WOSCC’s literature analysis wire, the VOSviewer 1.6.16, and CiteSpace 5.1.3 were used to conduct the analysis.ResultsA total of 785 publications containing 206 reviews and 579 articles are included in the sample. The leading authors are Iacopo Olivotto, Paolo G. Camici, and Carl J. Pepine. The most productive institutions are the University of Florence, Cedars Sinai Medical Center, and Harvard University. The most productive countries are the USA, Italy, and England. There are a total of 237 journals that contribute to this field, and the leading journals in our study were the International Journal of Cardiology, the European Heart Journal and the JACC. From 2012 to 2021, the top three most-cited articles focused on the association between HFpEF and CMD. The important keywords are heart failure, hypertrophic cardiomyopathy, chest pain, women, coronary flow reserve (CFR), endothelial dysfunction and prognostic value. “Positron emission tomography” shows the strongest burst strength, followed by “blow flow” and “artery.” The keywords that started to burst from 2015 are particularly emphasized, including “heart failure,” “coronary flow reserve,” and “management.”ConclusionStudies about CMD are relatively limited, and the largest contribution comes from the USA, Italy and England. More studies are needed, and publications from other countries should be enhanced. The main research hotspots in the CMD field include CMD in patients with HFpEF, sex differences, the new methods of diagnosis for CMD, and the effective treatment of CMD. Attention should be given to CMD in patients with HFpEF, and untangling the association between CMD and HFpEF could be helpful in the development of physiology-stratified treatment for patients with CMD and HFpEF.